Analysis of hepatocyte growth factor immunostaining in the placenta of HIV-infected normotensive versus preeclamptic pregnant women. (August 2018) - Cele, S.B.; Odun-Ayo, F.; Onyangunga, O.A.; Moodley, J.; Naicker, T.
Abstract: Objective: Hepatocyte Growth Factor (HGF) plays a role in the migration and morphogenesis of different cell types and tissues. Preeclampsia (PE) is associated with deficient trophoblast invasion and placental insufficiency; hence HGF production is expected to be compromised. This study therefore aimed to immunolocalize and morphometrically analyse placental HGF in normotensive versus PE pregnancies stratified by HIV status and gestational age. Study design: Normotensive (N; n = 40) and preeclamptic (PE; n = 80) women were stratified by HIV status (HIV- and HIV+), and gestational age i.e. early onset of PE (EOPE; <34 weeks) and late onset of PE (LOPE; ≥34 weeks). Placental tissues were stained using conventional immunohistochemistry, performed using mouse anti-human HGF antibody. Morphometric image analysis was performed using Zeiss Axio-Vision software. Results: HGF was immuno-localized within the syncytiotrophoblast, cytotrophoblast, endothelial and fibroblast-like cell populations of both conducting and exchange villi. Based on pregnancy type, HGF immunoexpression within the conducting villi was significantly different between N vs EOPE ( p = 0.0372) and EOPE vs LOPE ( p = 0.0006). Within the exchange villi, no significant difference of HGF immunostaining was noted between N vs EOPE and N vs LOPE. A down-regulation of HGF immuno-expression was observed in LOPE compared to other groups within both villi types, albeit non-significant. Based on HIV status, no significant difference in HGF immuno-expression was demonstrated between HIV- vs HIV + within the exchange and conducting villi. However, the expression of HGF in HIV- group was elevated in both villi types. Across the groups, a significant difference was found between N+ vs EOPE- ( p  = 0.0207), EOPE+ vs LOPE- ( p = 0.0036) and EOPE- vs LOPE- ( p = 0.0016) of the conducting villi while no significant difference was found within the exchange villi. Conclusion: This novel study demonstrates that HGF was two-fold higher in conducting compared to exchange villi irrespective of the pregnancy type. HIV infection does not influence HGF expression within the conducting and exchange villi. The HGF/c-MET receptor complex may modulate the ligand expression within the placenta.